Development of Two-Axis Rotational Small Ball Miller for Powder Metallurgy Applications - Fisal, Ahmad Syakir; Wan Muhammad, Wan Nur Azrina; Mohamad, Md. Nor Anuar (Progress in Aerospace and Aviation Technology, 2024)
In powder metallurgy, milling involves reducing solid metal into fine particles through grinding or crushing, which enhances its properties and applications. This study aims to fabricate a two-axis small milling machine for powder milling and to investigate the relationship between rotational speed and milling time effectiveness. The research begins with analyzing the requirements for powder metallurgy processes, focusing on factors like particle size distribution and homogeneity. SolidWorks software designs the milling machine, emphasizing optimal functionality for powder milling. The machine tests use aluminum chips, and an optical microscope assesses the post-milling particle sizes at various time intervals. The study employs two motors: a 12V DC motor and a 24V DC motor, each capable of reaching up to 1500 rpm. A potentiometer is used for user control and automation. After adding a fixed bar, particle sizes are measured at 1.02 mm for 500 rpm and 1.08 mm for 1500 rpm after two hours of milling. After an additional two hours, sizes decrease to 0.50 mm for 500 rpm and 0.56 mm for 1500 rpm, indicating effective particle size reduction with extended milling time. Results demonstrate that integrating a fixed bar into the two-axis small milling machine enhances particle size distribution and milling efficiency. Additionally, critical speed analysis underscores the importance of maximizing mill rotation for efficient milling operations. In conclusion, the two-axis small milling machine is successfully fabricated, demonstrating high quality and efficiency in powder metallurgy milling processes.